Potential of Inducible Nitric Oxide Synthase as a Therapeutic Target for Allergen-Induced Airway Hyperresponsiveness: A Critical Connection to Nitric Oxide Levels and PARP Activity - Salome’ V. Ibba; Mohamed A. Ghonim; Kusma Pyakurel; Matthew R. Lammi; Anil Mishra; A. Hamid Boulares (Mediators of Inflammation)
Although expression of inducible NO synthase (iNOS) in the lungs of asthmatics and associated nitrosative damage are established, iNOS failed as a therapeutic target for blocking airway hyperresponsiveness (AHR) and inflammation in asthmatics. This dichotomy calls for better strategies with which the enzyme is adequately targeted. Here, we confirm iNOS expression in the asthmatic lung with concomitant protein nitration and poly(ADP-ribose) polymerase (PARP) activation. We show, for the first time, that iNOS is highly expressed in peripheral blood mononuclear cells (PBMCs) of asthmatics with uncontrolled disease, which did not correspond to protein nitration. Selective iNOS inhibition with L-NIL protected against AHR upon acute, but not chronic, exposure to ovalbumin or house dust mite (HDM) in mice. Supplementation of NO by nitrite administration significantly blocked AHR in chronically HDM-exposed mice that were treated with L-NIL. Protection against chronic HDM exposure-induced AHR by olaparib-mediated PARP inhibition may be associated with the partial but not the complete blockade of iNOS expression. Indeed, L-NIL administration prevented olaparib-mediated protection against AHR in chronically HDM-exposed mice. Our study suggests that the amount of iNOS and NO are critical determinants in the modulation of AHR by selective iNOS inhibitors and renews the potential of iNOS as a therapeutic target for asthma.